Continuar os Antigos: Teatro de Marcello e Casa em Briteiros - Mariana de Soares e Barbieri Cardoso (2012)
"Continue the Ancients" is to understand how it was possible, today as in the past,intervene on pre-existing, with asset value without breaking the continuity of life ofbuildings (in this context, it should be noted that the word life takes a direction nearlypoetic), ie, get an old building retains its timeliness, achieved through a new refunctionalization,as well as updating the original function, so that it becomes thususeful for the present, without, however, on one hand lead to its distortion and,secondly, to its absolute sacralization.We search the utility needed from the building in the present, as at the time of theirprimary function in the past without resorting to his original refund (mimesis),whereas some conditions and needs of man and space are not the same today asyesterday . It is intended that the old building is so fundamental to the vital needs ofmodern man, as it was for the old man, answering the question of the reason to be ofarchitecture, related to the intervention on pre-existence.From the recognition of the analogy between the study of ancient (classical Romanarchitecture from the traditional Portuguese architecture) we develop, as acounterpoint, the comparison between the Baldassarre Peruzzi's intervention on anancient Roman theater in Rome, and the intervention of Fernando Távora about ahome's architecture dictates popular in northern Portugal, by identifying theconceptual similarity between the two interventions, with 500 years apart.With the aim of raising awareness about the problem of intervention on pre-existenceand to respect the old buildings, but making it useful to the present, we need to appealto the study of ancient architecture and its authors, proposing view in the art of thepast a means to intervene in the present.